تأثير الإيزوترتنوئين في علاج التهاب الجلد الزهمي - رومية عبد الحليم; إسماعيل محمد; شريبة ماريا (Latakia University Journal -Medical Sciences Series, 2019)
التهاب الجلد الزهمي هو مرض مزمن، ولا يتوفر حتى الآن علاج فعّال له. اقترحنا في بحثنا دراسة تأثيرالعلاج بالإيزوتريتنوئين بالطريق العام على التهاب الجلد الزهمي نظراً لتأثيره على إفراز الغدة الزهمية حيث يقلل من الإفراز الزهمي الذي يعتقد بدوره في الآلية الإمراضية لالتهاب الجلد الزهمي. حسب دراستنا كانت نسبة التحسن بعد 6 أشهر من انتهاء العلاج على الإيزوتريتنوئين بالطريق العام أكبر منها لدى تطبيق العلاج الموضعي. وبمتابعة المرضى على مدى 3 أشهر بعد إيقاف العلاج وجدنا أن نسبة النكس بعد العلاج بالإيزوتريتنوئين بالطريق العام أقل منها بشكل بسيط عند تطبيق العلاج الموضعي. كما وجدنا في المجموعة الأولى أن الإندفاعات الموضعة على الجذع و الثنيات هي الأكثر استجابةً للعلاج بالإيزوتريتنوئين بالطريق العام، يليها الوجه من حيث استجابته للعلاج، في حين كانت فروة الرأس أقل المناطق استجابةً للعلاج بالإيزوتريتنوئين. و في المجموعة الثانية وجدنا أن الثنيات و الجذع هي أيضاً أكثر المناطق استجابةً للعلاج في حين كانت نسب التحسن متقاربة في إصابات الوجه و فروة الرأس. حسب دراستنا قدم الإيزوتريتنوئين نتائج أفضل بشكل بسيط من نتائج العلاجات التقليدية الموضعية لالتهاب الجلد الزهمي. Seborrhoeic dermatitis is a chronic disease for which there is there is not an effective treatment available up till now. In our research, we suggest studying the effect of oral isotretinoin on seborrhoeic dermatitis, regarding its impact on the sebaceous gland in decreesing seborrhoeia, which might have a remarkable role in the pathology of seborrhoeic dermatitis. According to our study, after 6 months of treatment with oral isotretinoin the improvement rate was better than it was when applying topical treatment. A follow up of 3 months after stopping treatments, we found out that the recurrence rate with oral isotretinoin was slightly less than it was when applying topical treatment. We also found out in the first group that the trunk and intringinous areas are areas that best respond to the treatment with oral isotretinoin, followed by the face and the scalp respectively. In the second group, we found out that the trunk and intrintiginous areas are again areas that best respond to topical treatment, followed by the scalp and face. According to our study, isotretinoin gave slightly better results in the treatment of seborrhoeic dermatitis than ordinary topical treatments.